2017
DOI: 10.1039/c7ra01716b
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of silica nanoparticles/polycarboxylate superplasticizer modified graphene oxide on mechanical behavior and hydration process of cement composites

Abstract: In this paper, the graphene oxide (GO) modified by polycarboxylate superplasticizer (PC) (PC@GO) was decorated by silica nanoparticles (SiO 2 NPs) to form a hybrid structure of SiO 2 NPs/PC@GO. The asprepared SiO 2 NPs/PC@GO hybrid was incorporated in cement matrix for further reinforcement. The results show that SiO 2 NPs are uniformly distributed on the surface of GO nanosheets. The addition of SiO 2 NPs/PC@GO hybrid (1.5% SiO 2 and 0.02% GO by weight of cement) can increase the compressive strength by facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(31 citation statements)
references
References 28 publications
2
28
0
1
Order By: Relevance
“…It has often been stated that PCE copolymer prevents GO from aggregation both in Ca(OH) 2 electrolytes as well as in PC pastes [23,24,39,40]. This section investigates the validity of this claim for pastes with water-to-solid ratios of 0.4.…”
Section: Effect Of Go-pce On Alite and Pc Hydrationmentioning
confidence: 95%
See 2 more Smart Citations
“…It has often been stated that PCE copolymer prevents GO from aggregation both in Ca(OH) 2 electrolytes as well as in PC pastes [23,24,39,40]. This section investigates the validity of this claim for pastes with water-to-solid ratios of 0.4.…”
Section: Effect Of Go-pce On Alite and Pc Hydrationmentioning
confidence: 95%
“…17b-d. This also implies that the strength improvements reported in previous studies [23,24,39,40] resulted from the presence of GO aggregates rather than well-dispersed GO, as these studies only used 1% and 2% of PCE to mix GO with PC pastes.…”
Section: Effect Of Go-pce On Alite and Pc Hydrationmentioning
confidence: 98%
See 1 more Smart Citation
“…Cement can complete more than 55% hydration process aer 7 day curing as Wang et al reported, compared with about 60% hydration degree aer curing 28 days at same condition. [38][39][40] Additionally, 7 day curing is enough for silane coupling agent to react with cement based on previous research studies. 41,42 Aer curing, extra amount of the modied tail sealant at the bottom of cement paste was cleaned up, while the composite specimen was cut in half lengthwise to examine whether there was any interfacial transition zone formed.…”
Section: Cement-tail Sealant Interface Modied By Mptmsmentioning
confidence: 99%
“…The strong interfacial covalent bonding between C-S-H and the functionalized BNP sheets enhances the stress transfer thus improving the overall mechanical properties of the cementitious composites at BNP concentrations of 0.20-wt% and 0.40-wt%. As shown in Figs 22 and 23, the maximum percentage increase in the flexural strength of the BNPcementitious composite at 0.20-wt% is compared with that of several cementitious composites containing MWCNT and GO obtained from[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. As shown in these figures, overall, the BNP outperforms MWCNTs and GO.…”
mentioning
confidence: 99%